The Evaluation of Domestic Socially Responsible Investment Equity Funds Performance in Australia - Tang, Huiqiong (Auckland University of Technology, 2018)
In this paper, I analyse the performance of Australian domestic equity Socially Responsible Investment Funds (SRIFs). I construct a sustainability index based on negative screens, and use this index to evaluate the performance of SRIFs by employing the Jensen (1968) CAPM, Fama–French (1993) 3-factor and the Carhart (1997) 4-factor models. The results show that SRIFs outperform the SRI index between November 2002 and February 2018. I also find evidence that SRIFs have a preference for value stocks and past winners. No significant size bias is found over the entire period, although there is evidence of a bias towards small-firms during the 2007 Global Financial Crisis. Results of sub-period analysis show that SRIFs outperform the sustainability index both in the crisis and non-crisis periods, although the abnormal return during the crisis period is slightly higher than the non-crisis period. By employing the Henriksson and Merton (1981), and the Bollen and Busse (2001) models, I find that SRIF managers have positive stock-picking skills but no market timing abilities. I also compare the SRFIs’ performance with the Australia’s five most popular conventional indices (the ASX 100, ASX 200, ASX 300, MSCI Australian and All Ordinaries market return indices). The results document that the SRIFs also outperform the conventional benchmarks, while the magnitude of abnormal return is slightly lower than that from the sustainability index.
Keywords: Sustainability index; Fund performance evaluation; Capital asset pricing model; Socially responsible investment